2013
DOI: 10.1007/s15010-013-0411-5
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with antimalarial chemoprophylaxis in German soldiers: a 6-year survey

Abstract: The study confirms the findings of the French and US armies that even free-of-charge access to antimalarial medication will not lead to 100 % acceptance. The compliance problem is aggravated by the generally low age of deployed soldiers. Adequate counselling is crucial to increase adherence to antimalarial CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Previous studies about the relationships between CP compliance and other preventive measures against mosquito bites are contradictory. Whereas some studies showed no association [ 15 ] or even competition [ 16 ] with the use of personal protection measures, two other studies [ 17 , 18 ] reported that compliance with CP was positively associated with anti-mosquito measures, in line with the present study. In addition to the traditional malaria-related behaviours, the present study also suggests that more compliant subjects are also more likely to believe in CP effectiveness and to follow recommendations for doxycycline-monohydrate pill taking: pills should be taken at the same time each day, concurrently with food.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies about the relationships between CP compliance and other preventive measures against mosquito bites are contradictory. Whereas some studies showed no association [ 15 ] or even competition [ 16 ] with the use of personal protection measures, two other studies [ 17 , 18 ] reported that compliance with CP was positively associated with anti-mosquito measures, in line with the present study. In addition to the traditional malaria-related behaviours, the present study also suggests that more compliant subjects are also more likely to believe in CP effectiveness and to follow recommendations for doxycycline-monohydrate pill taking: pills should be taken at the same time each day, concurrently with food.…”
Section: Discussionsupporting
confidence: 89%
“…Yet, the risk of contracting malaria was perceived as high during the mission and was associated with correct compliance. This result was expected and other military studies reported that perceived threat due to mosquitoes or high perceived risk of malaria were associated with CP compliance [ 18 , 20 , 21 ]. In civilian studies, it has also been shown that travellers who perceived themselves as being at high risk of developing malaria after returning home [ 22 ] or travellers in high-risk malaria-endemic areas who had correctly perceived the level of risk [ 15 ] were more often compliant with CP.…”
Section: Discussionsupporting
confidence: 80%
“…Further, in spite of training and education in basic hygienic measures that are implemented before deployment, soldiers may tend to noncompliance if the temptation of appealing local foods coincides with monotonous food in the field canteen or perhaps delivery problems during the first phases of deployment. A previous study described noncompliance problems with antimalarial chemoprophylaxis on deployment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Malaria, travel-associated diarrhea as well as skin and sexually transmitted diseases are major health concerns on deployments in subtropical and tropical endemic settings [ 1 ]. Rapid diagnosis in case of suspected malaria is mandatory.…”
Section: Introductionmentioning
confidence: 99%